El Excentrico, 1976-06-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, CA, 2024)
June 5, 1976 [5 de junio de 1976]. Ano 27, No 5. Cover contains two portraits. One of Bart Collins and one of Allister McAlister. Collins was running for San Jose City Council and McAlister was running for Assemblyman at the 25th District. The cover was also a paid political advertisement.